Acoustic investigation of high-sensitivity spherical leak detector for liquid-filled pipelines. (March 2021) - Huang, Xinjing; Li, Zan; Li, Jian; Feng, Hao; Zhang, Yu; Chen, Shili
Abstract: Inner spherical detectors (SDs) can approach the leak point of a liquid-filled pipeline from the inside, and therefore potentially have very high leak detection sensitivity. This paper demonstrates the SD's high sensitivity of detecting tiny, continuous leak, from the perspective of systematic acoustic sensing via finite element simulations and experiments. The SD forms a closed air cavity which may acoustically resonate and thus amplify the transmitted sound induced by leaks. The original leak induced sound is broadband and can cover several meters, so the acoustically resonant, narrow-band and movable SD can always capture the leak signal while rolling forward in the pipeline. The SD has multiple acoustic modes, but the first one is the most stable and hardly susceptible to slight changes of the air cavity. The SD has acoustic directivity, but this does not hinder leak detection, because the SD will roll over several cycles while passing by the leak point. Characteristic frequencies of the SD are determined by the air cavity and independent of shell materials; nevertheless, the resin SD has better sound permeability than the aluminum SD, and therefore has higher sensitivity. Finally, the aluminum SD is used to detect the leak in a water-filled pipeline and achieves a high sensitivity up to 0.164 L/min.